ABILITIES AS A COMPONENT OF PEDAGOGICAL COMPETENCES’ EXPRESSION: TEACHERS’ ATTITUDE - Martišauskienė, Elvyda (Acta Paedagogica Vilnensia, 2010)
Abilities make up the most tangible part of a competence, where components of knowing, meaning, theory and practice merge. Following education policy documents and pedagogical practice, the cardinal groups of abilities have been identified, which are ranged by educators in the following order: abilities to communicate with learners, to diagnose achievements, to organise learning, to work in a team, to plan educator’s activity. The abilities of teaching to learn as well as abilities to perceive learners’ condition and to show respect to everybody as a personality are expressed strongest and meet the modern education paradigm. Teachers find abilities to work in teams and international groups or with other educators less important. This shows that new education strategies are not taking deep roots in practical activity. Other components of competence, such as knowledge and value-based principles, are mainly linked with abilities to communicate, plan educational activity and to diagnose achievements. Such links reveal a contact of them (knowledge and value-based principles) with the real education process. It was established that professional qualification and working experience have little effect on pedagogical abilities. Senior educators and those with a working experience from 1 to 10 years have a more positive attitude towards these indicators. Gender has a more relevant influence on formation of abilities. Women tend to be better at establishing favourable relations and at selecting most important material. However evaluations of abilities to share responsibilities, to work in teams or international groups are similar.